High-temperature-resistant modified black nylon laser penetrating material and preparation method thereof

By adding nylon material and other components to the polyamide material, the problem of poor compatibility with PP material under high temperature or solvent erosion is solved, and the laser transmittance and high temperature resistance of the material are improved.

CN119570242APending Publication Date: 2025-03-07FENGHUI NEW MATERIAL TECH (HUZHOU) CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411591523.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

Existing polyamide materials have poor compatibility with PP materials under high temperature or solvent erosion, resulting in poor laser transmissibility.

Method used

Add light-transmissive nylon material to the toner, combined with polyamide 66, polyamide 6, glass fiber and antioxidants to prepare a high-temperature-resistant modified black nylon laser penetration material.

Benefits of technology

The laser transmittance, high temperature resistance and solvent corrosion resistance of the material are improved, ensuring that the material appears black when melted and extruded at 260°C.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a high-temperature-resistant modified black nylon laser penetration material and a preparation method thereof, and belongs to the technical field of high polymer materials based on polyamide 66. The composite material is prepared from the following components in parts by weight: 50-55 parts of polyamide 66; 10 to 15 parts of polyamide 6; 30 parts of glass fiber; 0.1 to 1 part of an antioxidant; 0.1 to 1 part of toner; and 0 to 0.5 part of other components. The solvent red and the phthalocyanine blue are reasonably proportioned and blended to be black, and the nylon material with light transmission is added, so that the problem that the existing conventional black toner has poor compatibility with the PP material and is easy to separate out under the condition of high temperature or solvent erosion, so that the laser transmittance of the final material is poor is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of polymer materials based on polyamide 66, and specifically relates to a high-temperature resistant modified black nylon laser penetrating material and a preparation method thereof. Background Art

[0002] Polyamide is a polymer engineering plastic with multiple repeating polyamide groups on the main chain of the molecule. Polyamide has excellent mechanical properties, chemical resistance, heat resistance, and is easy to process. It is widely used in communication products, industrial and consumer products, automotive functional structural parts, and interior and exterior materials. Rapidly crystallized polyamide single hexagonal materials are widely used in thin-walled and complex structural injection molded parts, and are widely used in the automotive and industrial consumer product fields. At present, most polyamide materials have quality problems such as shrinkage, material shortage, and surface floating fibers when injection molding complex structures, especially large-sized parts, which greatly affect product performance and user experience.

[0003] Application No. 201210426832.0 A process for preparing a modified nylon material, wherein the obtained modified nylon PA66 and PA66+30% GF are mixed in equal proportions, and the obtained mixture is added to a twin-screw extruder through a main feed port, and the processing temperature is controlled at 230-260°C, and the screw speed is controlled at 300-400rpm. After melting, the modified nylon material product is extruded and granulated to obtain the modified nylon material product. The invention has good high temperature resistance and high strength.

[0004] The Chinese patent application number 201310587907.8 discloses a light polyolefin modified nylon material for automobile plastic parts, which contains the following raw materials in parts by weight: PA1212 100, SEBS 14-18, ultra-low density polyethylene 10-12, calcium stearate 4-5, stearic acid 1-2, polyethylene wax 6-8, magnesium hydroxide 6-9, chlorosulfonated polyethylene 8-12, dioctyl phthalate 3-5, angelica dahurica essential oil 1-2, and additives 12-15. The above invention combines the advantages of raw materials such as PA1212, SEBS, ultra-low density polyethylene, and chlorosulfonated polyethylene, and has good processing performance and mechanical properties. The prepared material is light and flexible, strong and firm, heat-resistant and aging-resistant, temperature-resistant, self-lubricating, and has good electrical insulation performance. It is safe and reliable and can be widely used in the production of various types of automobile plastic parts, and the added angelica dahurica essential oil gives the material a pleasant aroma.

[0005] However, the laser transmittance of the above materials and the materials in the prior art is poor, and the existing conventional black toner is mainly solvent black, which has poor compatibility with PP materials and is easy to precipitate under high temperature or solvent erosion, affecting the normal use of the product. Summary of the invention

[0006] The purpose of the present invention is to solve the problem that the existing conventional black toner has poor compatibility with PP materials and is easy to precipitate under high temperature or solvent erosion, resulting in poor laser transmittance of the final material by adding a nylon material with light transmittance to the toner.

[0007] In order to achieve the above technical objectives, the following technical solutions are provided. In the first aspect, a high temperature resistant modified black nylon laser penetrating material is prepared from the following components in parts by weight:

[0008] Polyamide 66, 50-55 parts;

[0009] Polyamide 6, 10-15 parts;

[0010] Glass fiber, 30 parts;

[0011] Antioxidant, 0.1-1 part;

[0012] Color powder, 0.1-1 part;

[0013] Others: 0 to 0.5 parts.

[0014] In the present technical solution, others include semi-aromatic nylon PA6I / 6T.

[0015] In an implementation manner, the toner is a pigment, and the pigment includes solvent red and phthalocyanine blue, which are mixed with nylon material; the nylon material is a semi-transparent material that can transmit laser light.

[0016] In an embodiment, the antioxidant is N,N′-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine.

[0017] In an embodiment, the glass fiber has a length of 3.0 mm to 4.5 mm and a diameter of 8 μm to 15 μm.

[0018] In an embodiment, the glass fiber has a length of 3.5 mm to 4.5 mm, a diameter of 8 μm to 15 μm, and a circular or elliptical cross section.

[0019] In an embodiment, the glass fiber has a length of 3.5 mm to 4.5 mm, a diameter of 8 μm to 15 μm, an elliptical cross section, and a ratio of the long to short diameters of the ellipse of 1:3 to 1:6.

[0020] In the second aspect, a method for preparing the high temperature resistant modified black nylon laser penetrating material is provided:

[0021] a. Raw material preparation: Take 50-55 parts of polyamide 66, 10-15 parts of polyamide 6, 30 parts of glass fiber, 0.1-1 parts of antioxidant, and 0.1-1 parts of color powder by weight, and store them separately in a measuring container and put them in the feeding area of ​​the stirring equipment;

[0022] b. Raw material mixing: polyamide 66 and polyamide 6 are first put into a mixing device for high-speed mixing. After mixing for 20-30 minutes, glass fiber is added. After mixing for another 10-20 minutes, antioxidant, color powder and other materials are added and stirred for another 5-10 minutes to form a mixture.

[0023] c. Drying: Place the mixture in step a in an air drying device at a temperature of 100°C to 110°C and dry for 2-5h;

[0024] d. Extrusion: The mixture in step b was fed laterally into a twin-screw extruder, wherein the screw speed was 40 r / min to 50 r / min, and the temperature of each section from the feed port to the die was 240 ℃, 280 ℃, 280 ℃, and 260 ℃;

[0025] e. Cooling: The molten mixture extruded from the twin-screw extruder in step c is introduced into a water tank for cooling, the temperature in the water tank is 10°C-20°C;

[0026] f. Pelletizing: The cooled mixture in step d is pelletized to prepare a composite material.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] The final product performance of this application is 60% laser transmittance, 328MPa bending strength, 230MPa tensile strength, and 1.9% tensile elongation at break. The product is black when melt-extruded at 260° through a reasonable ratio of pigments.

[0029] Moreover, while ensuring the comprehensive mechanical properties of the material, the material's high temperature resistance and solvent corrosion resistance are improved.

[0030] The composite material produced by the present invention can be applied to automobile engine peripherals and interior and exterior decoration products, has a friendly processing environment and meets the material selection requirements of major OEMs such as BYD and Chery. DETAILED DESCRIPTION

[0031] Below in conjunction with specific embodiment, further elaborate content of the present invention.It should be emphasized that these embodiments are only used for further explanation of the present invention, and can not be interpreted as limiting the scope of protection of the present invention.In addition, it should be understood that after reading the content described in the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope limited by the appended claims of the application.

[0032] Example 1: The high temperature resistant modified black nylon laser penetrating material of this example is composed of the following components by weight: 50 parts of polyamide PA66, 10 parts of polyamide PA6, 30 parts of glass fiber, 0.7 parts of N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl) hexamethylenediamine antioxidant and 1 part of toner. The toner contains pigments, including solvent red and phthalocyanine blue, wherein the preferred solvent red is a mixture of solvent red 52 and phthalocyanine blue, and then a small amount of nylon material is mixed, and the final product is black after mixing.

[0033] And the preparation steps of this embodiment are:

[0034] a. Raw material preparation: Take 50 parts of polyamide PA66, 10 parts of polyamide PA6, 30 parts of glass fiber, 0.7 parts of N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl) hexamethylenediamine antioxidant and 1 part of color powder by weight, store them separately in a measuring container, and place them in the feeding area of ​​the stirring equipment;

[0035] b. Raw material mixing: polyamide 66 and polyamide 6 are first put into a mixing device for high-speed mixing. After mixing for 20 minutes, glass fiber is added. After mixing for another 10 minutes, antioxidant, color powder and other materials are added and stirred for another 5 minutes to form a mixture.

[0036] c. Drying: Place the mixture in step a in an air drying device at a temperature of 100°C and dry for 3h;

[0037] d. Extrusion: The mixture in step b was fed laterally into a twin-screw extruder, wherein the screw speed was 40 r / min, and the temperature of each section from the feed port to the die was 240 ℃, 280 ℃, 280 ℃, 260 ℃;

[0038] e. Cooling: The molten mixture extruded from the twin-screw extruder in step c is introduced into a water tank for cooling, the temperature in the water tank is 20°C;

[0039] f. Pelletizing: The cooled mixture in step d is pelletized to prepare a composite material.

[0040] In this embodiment, the rotation speed of the device for high-speed mixing is 1500 rpm.

[0041] Example 2: The high temperature resistant modified black nylon laser penetrating material of this example is composed of the following components by weight: 55 parts of polyamide PA66, 15 parts of polyamide PA6, 30 parts of glass fiber, 0.5 parts of N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl) hexamethylenediamine antioxidant and 0.7 parts of toner. The toner contains a small amount of nylon material, and the dye includes solvent red and pigment blue, wherein the preferred solvent red is a mixture of CI solvent red 179 and pigment blue 15, and then a small amount of nylon material is mixed, and the final product is black after mixing.

[0042] And the preparation steps of this embodiment are:

[0043] a. Raw material preparation: Take 55 parts of polyamide PA66, 15 parts of polyamide PA6, 30 parts of glass fiber, 0.5 parts of N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl) hexamethylenediamine antioxidant and 0.7 parts of toner by weight, store them separately in a measuring container, and place them in the feeding area of ​​the stirring equipment;

[0044] b. Raw material mixing: polyamide 66 and polyamide 6 are first put into a mixing device for high-speed mixing. After mixing for 20 minutes, glass fiber is added. After mixing for another 10 minutes, antioxidant, color powder and other materials are added and stirred for another 5 minutes to form a mixture.

[0045] c. Drying: Place the mixture in step a in an air drying device at a temperature of 100°C and dry for 3h;

[0046] d. Extrusion: The mixture in step b was fed laterally into a twin-screw extruder, wherein the screw speed was 40 r / min, and the temperature of each section from the feed port to the die was 240 ℃, 280 ℃, 280 ℃, 260 ℃;

[0047] e. Cooling: The molten mixture extruded from the twin-screw extruder in step c is introduced into a water tank for cooling, the temperature in the water tank is 10°C;

[0048] f. Pelletizing: The cooled mixture in step d is pelletized to prepare a composite material.

[0049] In this embodiment, the rotation speed of the device for high-speed mixing is 1500 rpm.

[0050] Example 3: The high temperature resistant modified black nylon laser penetrating material of this example is composed of the following components by weight: 55 parts of polyamide PA66, 15 parts of polyamide PA6, 30 parts of glass fiber, 0.5 parts of N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl) hexamethylenediamine antioxidant and 0.7 parts of toner. The toner contains a small amount of nylon material, and the dye includes solvent red and pigment blue, wherein the preferred solvent red is a mixture of CI solvent red 179 and pigment blue 15, and then a small amount of nylon material is mixed, and the final product is black after mixing.

[0051] And the preparation steps of this embodiment are:

[0052] a. Raw material preparation: Take 55 parts of polyamide PA66, 15 parts of polyamide PA6, 30 parts of glass fiber, 0.5 parts of N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl) hexamethylenediamine antioxidant and 0.7 parts of toner by weight, store them separately in a measuring container, and place them in the feeding area of ​​the stirring equipment;

[0053] b. Raw material mixing: polyamide 66 and polyamide 6 are first put into a mixing device for high-speed mixing, glass fiber is added after mixing for 30 minutes, antioxidant, color powder and other materials are added after mixing for another 20 minutes, and then stirred for another 10 minutes to form a mixture;

[0054] c. Drying: Place the mixture in step a in an air drying device at a temperature of 110°C and dry for 2h;

[0055] d. Extrusion: The mixture in step b was fed laterally into a twin-screw extruder, wherein the screw speed was 40 r / min, and the temperature of each section from the feed port to the die was 240 ℃, 280 ℃, 280 ℃, 260 ℃;

[0056] e. Cooling: The molten mixture extruded from the twin-screw extruder in step c is introduced into a water tank for cooling, the temperature in the water tank is 10°C;

[0057] f. Pelletizing: The cooled mixture in step d is pelletized to prepare a composite material.

[0058] In this embodiment, the rotation speed of the device for high-speed mixing is 1500 rpm.

[0059] The light transmittance test method of the above embodiment is tested by using the test method in GB / T7247.1-2012 9.2 "Safety of Laser Products Part 1. Equipment Classification and Requirements".

[0060] The following table shows the test results of the light transmittance of the embodiments.

[0061] Test items Embodiment 1 Embodiment 2 Embodiment 3 Laser transmittance (%) 63.0% 76.4% 63.9%

Claims

1. A high temperature resistant modified black nylon laser penetrating material, characterized in that: The composite material is prepared from the following components in parts by weight: Polyamide 66, 50-55 parts; Polyamide 6, 10-15 parts; Glass fiber, 30 parts; Antioxidant, 0.1-1 part; Color powder, 0.1-1 part; Others: 0 to 0.5 parts.

2. The high temperature resistant modified black nylon laser penetrating material according to claim 1, characterized in that: The toner is a pigment, which includes solvent red and phthalocyanine blue, and is mixed with nylon material; the nylon material is a semi-transparent material through which laser light can pass.

3. The high temperature resistant modified black nylon laser penetrating material according to claim 1 or 2, characterized in that: The antioxidant is N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine.

4. The high temperature resistant modified black nylon laser penetrating material according to claim 3, characterized in that: The length of the glass fiber is 3.0 mm to 4.5 mm, and the diameter is 8 μm to 15 μm.

5. The high temperature resistant modified black nylon laser penetrating material according to claim 3, characterized in that: The length of the glass fiber is 3.5 mm to 4.5 mm, the diameter is 8 μm to 15 μm, and the cross section is circular or elliptical.

6. The high temperature resistant modified black nylon laser penetrating material according to claim 3, characterized in that: The length of the glass fiber is 3.5 mm to 4.5 mm, the diameter is 8 μm to 15 μm, and the cross section is elliptical, with the ratio of the long and short diameters of the ellipse being 1:3 to 1:

6.

7. The method for preparing the high temperature resistant modified black nylon laser penetrating material according to any one of claims 1 to 6, characterized in that: a. Raw material preparation: Take 50-55 parts of polyamide 66, 10-15 parts of polyamide 6, 30 parts of glass fiber, 0.1-1 parts of antioxidant, and 0.1-1 parts of color powder by weight, and store them separately in a measuring container and put them in the feeding area of ​​the stirring equipment; b. Raw material mixing: polyamide 66 and polyamide 6 are first put into a mixing device for high-speed mixing. After mixing for 20-30 minutes, glass fiber is added. After mixing for another 10-20 minutes, antioxidant, color powder and other materials are added and stirred for another 5-10 minutes to form a mixture. c. Drying: Place the mixture in step a in an air drying device at a temperature of 100°C to 110°C and dry for 2-5h; d. Extrusion: The mixture in step b was fed laterally into a twin-screw extruder, wherein the screw speed was 40 r / min to 50 r / min, and the temperature of each section from the feed port to the die was 240 ℃, 280 ℃, 280 ℃, and 260 ℃; e. Cooling: The molten mixture extruded from the twin-screw extruder in step c is introduced into a water tank for cooling, the temperature in the water tank is 10°C-20°C; f. Pelletizing: The cooled mixture in step d is pelletized to prepare a composite material.

Citation Information

Patent Citations

  • Preparation process of modified nylon material

    CN102964826A

  • A kind of lightweight polyolefin modified nylon material for automobile plastic parts

    CN103665861B

  • Polyamide composite for improving laser weldability

    CN111138852A

  • Antistatic nylon composite material for laser welding and preparation method thereof

    CN116355398A

  • Black laser welding polyamide resin composition and molded article using the same

    JP2008266434A